Analysis of Legal and Social Implications Related to the Visa Free Policy for Visiting Foreign Citizens: A Meta-Analysis in Bali, Indonesia - Sahril Muhamad Maulani; Nur Rizki, Radha Evi (Arkus, 2024)
The free visit visa (BVK) policy for foreign nationals (WNA) in Bali, Indonesia, has become an important instrument in encouraging tourism. However, this policy also gives rise to complex dynamics of social norms. This research aims to analyze existing studies regarding social norms related to BVK in Bali through a meta-analysis approach. This research uses a meta-analysis method by collecting data from various relevant empirical studies, both qualitative and quantitative, published between 2018-2024. Keywords used in the search included "social norms," "visa-free policy," "Bali," "tourism," and "Indonesia." Selected studies were then systematically analyzed to identify key themes and emerging patterns. The meta-analysis results show that there are various social norms related to BVK in Bali. Several norms support this policy, such as norms of friendliness and openness towards foreigners. However, there are also norms that have the potential to cause conflict, such as norms relating to politeness, customs and public order. This research provides a deeper understanding of the complexity of social norms related to BVK in Bali. These findings have important implications for stakeholders in formulating more effective and sustainable policies, as well as for the Balinese people in facing social changes that occur as a result of tourism.